(untitled) (UNED Research Journal, 2017)
The bat Trinycteris nicefori is uncommon and some countries have declared their populations "vulnerable to extinction". Only three of 46 localities historically report T. nicefori individuals on the Pacific coast of the American continent, one of them in the North Pacific of Costa Rica (Higueron River, Cañas Guanacaste). Between 2014 and 2016, two individuals were captured in two caverns of Barra Honda National Park, Costa Rica. This is the first record of this species for the Peninsula and the second for the Pacific coast of the country. The abundance of caves in the Protected Natural Area may contribute to the presence of this species.